Correlation between RON and catalytic cracking naphtha composition - Ragone, Giuseppina; Zambrano, José; Lugo, Helí (Rev. Téc. Fac. Ing. Univ. Zulia)
This work describes the development of a correlation between the Research Octane Number and the catalytic cracking naphtha composition. The correlation was developed using a non-ideal model. The adjustable parameters in the model were determined by multiple regression using 67 naphtha samples produced at Amuay Fluid Catalytic Cracking Unit (Falcon State, Venezuela). This correlation is useful to predict catalytic cracking naphtha RON, using its composition determined by chromatography. The confidence limit of this prediction is Ó 0.6 number. With the information of the octane-composition relationship, it is possible to establish strategies for catalytic cracking naphtha RON enhancement.